Humanism in Bhupen Hazarika’s Songs: A Critical Review - Bhupen Gogoi (International Journal of Advanced Science and Technology, 2020)
Music is the highest art, and to those who understand, it is the highest worship’- Swami Vivekananda. Bhupen Hazarika was an Indian artist, famously referred to as the uncrowned king of the cultural world of North-East India. He was a humanist. He loved his motherland Assam so much. Hazarika dedicated his whole life to the people of Assam, its vivid culture, and natural beauty. He was a poet, music composer, singer, actor, journalist, author, and filmmaker. Hazarika has sung numerous Assamese, Bengali, and Hindi songs. Most of his songs are marked by themes of humanity and universal brotherhood. He wanted to create a beautiful society where there will be no bar between people of different castes, color, or religious groups. During his lifetime, he gives us a lot and dedicated himself to establish the essence of humanity and social integrity.